The Role of Music in The Education of Youth - Israil Saidumarov (Scientific Trends, 2024)
This article provides analytical information on the role and importance of music in the upbringing of the growing young generation and its harmonious development as a person, and its importance from ancient times to the present day.
Keywords: Human, personality, upbringing, education, music, lesson, training, art, pedagogy.